Cableways in forestry - Neruda, Jindřich; Nevrkla, Pavel; Simanov, Vladimír; Staněk, Luboš; Zemánek, Tomáš (Mendelova univerzita v Brně, 2023)
The publication Cableways in forestry discusses the basic technical solutions of cable transport installations, cables, chains and chokers. It also focuses on appropriate work procedures and work safety. At the end of the publication, the production program of the Czech cableways manufacturer Křtiny research station is mentioned. The publication is divided into seven chapters: Technical development of cable transport installations, Terminology, Classification of cable transport installations, Main parts of cable transport installations, Work technique at timber yarding by means of CTIs, Designing CTI and Cable transport installations of the Křtiny research station (Czech Republic). The publication is intended for the professional public and students of high schools and universities.
Keywords: cableways; forestry; timber yarding; OHS